2020
DOI: 10.1155/2020/2603873
|View full text |Cite
|
Sign up to set email alerts
|

The Adenosine A2A Receptor Agonist Accelerates Bone Healing and Adjusts Treg/Th17 Cell Balance through Interleukin 6

Abstract: The aim of this study was to explore the effect of adenosine A2A receptor agonists on fracture healing and the regulation of the immunity system after bone fracture. We implanted fibrin gel containing adenosine A2A receptor agonist CGS 21680/inhibitor ZM 241385/saline locally in rat tibial fracture models, finding that the adenosine A2A receptor agonist could promote fracture healing. At the same time, the adenosine A2A receptor agonist decreased the level of IL-6 in blood and the fracture area, increased Treg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 50 publications
2
23
1
Order By: Relevance
“…PASS 11.0 software was used to calculate the sample size. We referred to the previous literature by using burning periosteum to make bone nonunion rat model and all of them were successful [ 11 , 15 , 16 ]. In addition, there was no report about making model failure.…”
Section: Methodsmentioning
confidence: 99%
“…PASS 11.0 software was used to calculate the sample size. We referred to the previous literature by using burning periosteum to make bone nonunion rat model and all of them were successful [ 11 , 15 , 16 ]. In addition, there was no report about making model failure.…”
Section: Methodsmentioning
confidence: 99%
“…For the in vivo experiments, the tibia fracture nonunion model was used and the sample size was estimated by referring to previous studies on the ADA2AR promotion of fracture healing, because there have been no studies of how the ADA2AR accelerates angiogenesis in bone healing. 2,26 The study showed that the ADA2AR promoted bone healing (the rate of increase was 100%) and the fracture healing rate of the control group was 0 at 8 weeks. 2,26 In addition, α was set as 0.05 (two-sided), the failure rate of the model was 10%, and 1-β was set as 0.80.…”
Section: Animal Sample Sizementioning
confidence: 96%
“…Bone fracture is a common cause of disability and the nonunion rate is approximately 5-10% despite patients receiving active treatment. [1][2][3] Poor vascularization leads to nonunion, and vascular endothelial cells (VECs) are known to be critical to nonunion. [3][4][5][6] Damaged VECs release many bioactive factors, which accelerate VEC proliferation and migration during the initial process of angiogenesis after bone fracture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations